Teacher Development in Learning Management for Enhancing Students’ Analytical Thinking in NonPhoSriWittayakom - Sirimala, Damrong (Journal of Graduate MCU KhonKaen Campus, 2024)
The purposes of this study were to 1) to study current and problem conditions of teachers’ learning management for enhancing students’ analytical thinking 2) to develop teachers’ learning management for enhancing students’ analytical thinking based on alternatives and participatory action plan, and 3) to follow up teachers’ developmental results for enhancing students’ analytical thinking. This is a participatory action research. The target group for this study consists of school administrators, teachers, and students. It is divided into 26 research participants and 63 informants. The research process is conducted in three phases: Phase 1 - Research Preparation, Phase 2 - Research Implementation with two cycles, and Phase 3 - Development Summary. The research tools used for data collection include questionnaires, self-assessment forms, behavior observation forms, interviews, and supervision logs. Qualitative data analysis is conducted using content analysis, while quantitative data is analyzed using statistical methods such as mean, percentage, and standard deviation. The research findings were as follows; 1. A study of current and problem conditions of teachers’ learning management for enhancing students’ analytical thinking in Non Pho Sri Wittakom school were 1) according to current condition, the students were not enhanced analytical thinking. and 2) according to problem condition, teachers were not developed to enhance students’ analytical thinking. 2. The development of teachers’ learning management for enhancing students’ analytical thinking based on alternatives and participatory action plan in phase 1: the guidelines for development consisted of 1) workshop 2) supervision and monitoring and in phase 2: the guideline for development was coaching supervision. 3. The results of teacher development in learning management for enhancing students’ analytical thinking were as follows; 1) teachers’ awareness toward learning management for enhancing students’ analytical thinking was at highest level, 2) teachers’ abilities of creating their lesson plans for enhancing students’ analytical thinking was at highest level, and 3) the improvement of students’ learning behaviors for enhancing students’ analytical thinking was at highest level.